2021
DOI: 10.1523/eneuro.0398-21.2021
|View full text |Cite
|
Sign up to set email alerts
|

Task Modulation of Single-Neuron Activity in the Human Amygdala and Hippocampus

Abstract: The human amygdala and hippocampus are critically involved in various processes in face perception. However, it remains unclear how task demands or evaluative contexts modulate processes underlying face perception. In this study, we employed two task instructions when participants viewed the same faces and recorded single-neuron activity from the human amygdala and hippocampus. We comprehensively analyzed task modulation for three key aspects of face processing and we found that neurons in the amygdala and hip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 63 publications
1
16
0
Order By: Relevance
“…Our own reports have further revealed context-dependent modulation of some of these brain areas during judgment of facial trustworthiness and dominance [4,121]. In particular, the human amygdala plays a critical role in social perception [17,122] and encode various social trait judgments of faces, which has been supported by lesion [123], fMRI [4,105,124], and neurophysiology [121] studies. It is worth noting that these prior functional studies primarily focused on facial trustworthiness; however, humans use hundreds of different trait words to describe spontaneous trait judgments of faces [114,116,117] and automatically evaluate faces on multiple trait dimensions simultaneously.…”
Section: Neural Correlates Of Social Trait Judgmentmentioning
confidence: 53%
See 1 more Smart Citation
“…Our own reports have further revealed context-dependent modulation of some of these brain areas during judgment of facial trustworthiness and dominance [4,121]. In particular, the human amygdala plays a critical role in social perception [17,122] and encode various social trait judgments of faces, which has been supported by lesion [123], fMRI [4,105,124], and neurophysiology [121] studies. It is worth noting that these prior functional studies primarily focused on facial trustworthiness; however, humans use hundreds of different trait words to describe spontaneous trait judgments of faces [114,116,117] and automatically evaluate faces on multiple trait dimensions simultaneously.…”
Section: Neural Correlates Of Social Trait Judgmentmentioning
confidence: 53%
“…A meta-analysis of 29 neuroimaging studies for social evaluation of faces has revealed that across negative face evaluations the most consistent activations are in the bilateral amygdala whereas across positive face evaluations the most consistent activations are in the medial prefrontal cortex (mPFC), pregenual anterior cingulate cortex (pgACC), medial orbitofrontal cortex (mOFC), left caudate, and nucleus accumbens (NAcc) [120]. Our own reports have further revealed context-dependent modulation of some of these brain areas during judgment of facial trustworthiness and dominance [4,121]. In particular, the human amygdala plays a critical role in social perception [17,122] and encode various social trait judgments of faces, which has been supported by lesion [123], fMRI [4,105,124], and neurophysiology [121] studies.…”
Section: Neural Correlates Of Social Trait Judgmentmentioning
confidence: 74%
“…124 Our own findings have further revealed context-dependent modulation of some of these brain areas during judgment of facial trustworthiness and dominance. 8,120 In particular, the human amygdala plays a critical role in social perception 28,125 and encodes various social trait judgments of faces, which has been supported by lesion studies, 126 fMRI studies, 8,105,119 and neurophysiology studies. 120 It is worth noting that these prior functional studies primarily focused on facial trustworthiness; however, humans use hundreds of different trait words to describe spontaneous trait judgments of faces 115,117,118 and automatically evaluate faces on multiple trait Our recent study has addressed this need, using a comprehensive face space (i.e., measuring trait judgments representative of the warmth-competence-femininity-youth model) (Figure 5A) and singleneuron recordings in the human amygdala and hippocampus.…”
Section: Fmri and Human Single-neuron Recordings Reveal Neural Correl...mentioning
confidence: 90%
“…An early experiment in humans did report a small number of MTL neurons that showed responses to words and also to unrelated faces (Heit et al, 1988). Some studies in humans have examined responses to the same stimuli based on task demands, for example, finding differences in responses across regions to different task demands when viewing the same faces (Cao, Todorov, et al, 2022). In another experiment, asking participants to flexibly switch between a recognition memory and categorization task led to different population-level representations of the task demands in the medial frontal cortex (Minxha et al, 2020).…”
Section: Introductionmentioning
confidence: 99%